RNA interference functions and mechanisms in animals - Carthew, Richard (Henry Stewart Talks, 2017)
Introduction to selfish genetic elements, RNAi as a mechanism to defend against selfish gene replication, The Argonaute cycle of RNA binding, RNAi represses both viruses and transposable elements, Post-transcriptional cleavage of mRNAs, Applications of RNAi, Dicer and its cofactors process and load RNA into Argonaute, Distinct Dicer mechanisms for viral and transposon RNA, Virus counter-measures to Dicer, mRNAs evolved as gene regulators from RNAi